The molecular mechanism underlying the induction of hepatic MRP3 expression and function by omeprazole‡. (11th February 2015) - Pan, Yu‐Qin; Mi, Qiong‐Yu; He, Bang‐Shun; Zhao, Shu‐Li; Tai, Ting; Xie, Hong‐Guang
Abstract Previous work has indicated that there is increased protein expression of multidrug resistance‐associated protein 3 (MRP3) in the liver samples of patients treated with omeprazole compared with those who were not. However, evidence is still lacking to show the mechanisms underlying that induction. This study aimed to assess changes in the fold‐induction of MRP3 mRNA and protein expression over controls in omeprazole‐treated HepG2 cells after transient transfection of human MRP3 siRNA, or after pretreatment with actinomycin D (Act‐D). Furthermore, MRP3 siRNA knock‐down or MRP‐specific inhibition (indomethacin) was used to determine whether the MRP3 protein induced by omeprazole possessed an enhanced efflux transport. The results demonstrated that omeprazole induced MRP3 mRNA and protein expression in a concentration‐ and time‐dependent manner. Moreover, that induction was almost completely abolished by the addition of human MRP3 siRNA and also by pretreatment with Act‐D, respectively. In addition, the decay rate of MRP3 mRNA in vehicle‐ and omeprazole‐treated cells was similar in the presence of Act‐D, suggesting transcriptional up‐regulation of MRP3 mRNA expression by omeprazole. Most importantly, omeprazole induced MRP3 efflux transport activity, as measured by the 5‐carboxyfluorescein assay in the absence and presence of human MRP3 siRNA or indomethacin. It is concluded that omeprazole can induce MRP3 mRNA and protein expression and enhance MRP3 efflux transport activity through transcriptional up‐regulation, and that omeprazole can also induce other MRP transporters. Copyright © 2015 John Wiley & Sons, Ltd.